111k views
0 votes
I don't understand how to do this

I don't understand how to do this-example-1
User Evdama
by
5.1k points

2 Answers

2 votes

Answer: the first option is the correct answer.

Explanation:

The center of the circle is (-6, -3)

The formula for determining the equation of a circle us expressed as

(x - h)² + (y - k)² = r²

Where

r represents the radius of the circle

h and k represents the x and y coordinates of the center of the circle. Comparing with the given points,

h = - 6 and k = - 3

Radius, r = 12

Substituting into the formula, it becomes

(x - h)² + (y - k)² = r²

(x - - 6)² + (y - - 3)² = 12²

(x + 6)² + (y + 3)² = 144

User Kodiologist
by
5.6k points
3 votes

Answer:

It is the first option

(x + 6)^2 + (y + 3)^2 = 144

Explanation:

the formula of a circle is given by

(x - h)^2 + (y - k)^2 = r^2

h would be the value of the center in x

k would be the value of the center in y

r = would be the radio

replacing with the given values

h = -6

k = -3

r = 12

(x - (-6))^2 + (y - (-3))^2 = 12^2

(x + 6)^2 + (y + 3)^2 = 144

User Nikolai Savulkin
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.